The Fundamental Rules of Risk Management. - Lewis, Nigel Da Costa (CRC Press, 2012)
Section I: The Behavioral Foundations of Risk ManagementUnreason Is the Even Eviler Twin Brother of GreedA Word to the Wise-You Cannot Rely on the Flynn EffectThe Unintended Consequences of the Glad GameBut You Have to Remember Ivar Kreuger of Kalmar!The Maleficent Hand of the Men in Gray SuitsUnreason Abounds in Places Where It Must NotThe Conspiratorial RegulatorThe Apathetic RegulatorThe Unpalatable Truth about Risk ManagementA Rather Vulgar, But Common, Perception of Risk ManagementThe Emperor of Risk, His Lyre, and the PalatineThe Utter and Total Redundancy of Financial Risk ManagementThe.